The Qadian Ahmadiyah in Riau: History, Existence, and Development in the 20th Century - Azhari, Alhamra; Machmudi, Yon (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2024)
The focus of this paper reconstructs how the history and who was the carrier of the Qadian Ahmadiyah sect in the early days of its entry into Riau Province and examines its distribution areas. As well as explaining the development of the existence of the Qadian Ahmadiyah Jema'at in Riau Province, which faced pressure from the government and society. The research method used is the historical method through four stages, namely first, heuristics, which is the stage of collecting data in the form of documents or books, articles, journals, and interviews. Second, source criticism, namely testing data by conducting internal and external criticism of data from various sources. Third, interpretation, which is the interpretation of data so that it becomes a meaningful fact. The last stage is historiography or historical writing. The results showed that the entry of the Qadian Ahmadiyah teachings into Riau Province was influenced by Ahmadis from West Sumatra because Riau Province is an overseas area from West Sumatra. As a result, Ahmadiyah teachings spread in this region through close relationships between these migrants. Second, the entry of Qadian Ahmadiyah teachings in Riau Province was also influenced by Qadian Ahmadis from Yogyakarta who transmigrated and settled in Kota Bangun Village, Kampar, Riau.